A plant Bro1 domain protein BRAF regulates multivesicular body biogenesis and membrane protein homeostasis - Jinbo Shen (Nature Portfolio, 2018)
The ESCRT complex contributes to selective vacuolar degradation of membrane proteins. Here, the authors show that the plant-specific BRAF protein negatively regulates intraluminal vesicle formation and membrane protein degradation by preventing FREE1 binding to the ESCRT-I complex protein Vps23.